Homoseksualitas Masa Kini: Suatu Tinjauan Menurut Etika Kristen - Suzanna Hilaria Halim (Veritas : Jurnal Teologi dan Pelayanan, 2017)
Homosexuality, in this day and age, is not understood as a kind of behavior, but as a sexual orientation that emerges out of human identity and is beyond human will. As a result, people consider homosexuality to be a normal lifestyle and do not perceive of it as sinful behaviour. Evaluations, garnered from both biblical and theological perspectives, are examined to answer the complicated questions related to this topic and conclude that homosexuality is sin.